A comparison of cardiomyocyte cytotoxic mechanisms for 5-fluorouracil and its pro-drug capecitabine. (January 2015) - Eskandari, Mohammad Reza; Moghaddam, Faezeh; Shahraki, Jafar; Pourahmad, Jalal
Abstract 1. 5-Fluorouracil (5-FU) and its prodrug capecitabine are key chemotherapeutic agents in the treatment of many gastrointestinal tract adenocarcinomas. In addition to their beneficial antitumor effects, they also possess undesired cardiac toxicity. In the present study, we investigated the cytotoxic mechanisms of 5-FU and capecitabine in freshly isolated rat cardiomyocytes. 2. 5-FU and capecitabine cytotoxicities were associated with reactive oxygen species (ROS) formation, lipid peroxidation and rapid glutathione depletion. Increased intracellular ROS could target mitochondria, and our findings confirmed that the cardiomyocytes mitochondrial membrane potential (ΔΨm) was rapidly decreased by 5-FU and capecitabine. Mitochondrial dysfunction subsequently initiates downstream events that trigger caspase-3 activation, and our results showed that 5-FU and capecitabine activated caspase-3 which leads to apoptosis or necrosis. However, 5-FU acted much more powerful than capecitabine at inducing several cytotoxicity markers in heart cardiomyocytes. In addition, 5-FU but not capecitabine caused lysosomal membrane leakiness when it was incubated with cardiomyocytes. All cytotoxicity markers were prevented by antioxidants, ROS scavengers, mitochondrial permeability transition (MPT) pore sealing agents and lysosomotropic agents. 3. Our findings showed that the cytotoxic action of 5-FU and capecitabine on cardiomyocytes are mediated by oxidative stress and subsequent mitochondrial dysfunction which causes caspase-3 activation and cell death.